ОСИП СЕНКОВСКИЙ И ВИССАРИОН БЕЛИНСКИЙ КАК «ПЕРСОНАЖИ» РОМАНОВ СТЕПАНА БУРАЧКА - Сартаков, Егор (Przegląd Rusycystyczny, 2016)
Egor Sartakov OSIP SENKOVSKY AND VISSARION BEL INS KY AS “CHARACTERS ” OF STEPAN BURACHOK’S NOVELS S u m m a r y The article analyzes two novels of forgotten in our days conservative journalist and writer Stepan Burachok — A tale without a title (forbidden by censorship in 1838, discovered in manuscript department of Institute of Russian Literature of Russian Academy of Sciences) and Heroes of our time (published in 1845 in “Mayak” magazine). In both works with a pronounced publicistic character prototypes of the main characters appear to be famous journalists of that time, with whom Burachok had a hidden polemic — Osip Senkovsky and Vissarion Belinsky. The study of Burachok’s works in this context allowed, on the one hand, to expand our understanding of tactics of literary and journalistic struggle of 1830–1840, and on the other — to specify the role of individual journalists in this fight.